Experimental and numerical investigation into iron ore reduction in packed beds. (2nd February 2016) - Peters, B.; Hoffmann, F.; Senk, D.; Babich, A.
Abstract: The objective of this contribution is to investigate into indirect iron reduction in a packed bed on both an experimental and a numerical level. For this purpose experiments of a packed bed of iron ore particles in a laboratory-scale reactor were carried out. Inflow conditions in terms of temperature and reducing gas composition were subject to change and the integral behaviour of the reactor was qualified by measuring the outflow conditions. In particular, the composition of the off-gas was analysed to determine the overall reduction degree of the packed bed. The numerical technique is based on a coupled DEM-CFD approach, in which the iron ore is treated as discrete particles and the flow of reducing gas is described by classical CFD. Each particle is characterised by its thermodynamic state, that is determined by solving one-dimensional and transient differential conservation equations for mass and energy. In conjunction with a reaction mechanism for iron reduction through carbon monoxide, the spatially and temporarily dependent reduction degree for each individual particle is resolved. Integrating over all particles yields the integral behaviour of the reactor. These results were compared to measurements and very good agreement was obtained. Abstract : Highlights: Particle resolved heterogeneous reduction of iron oxide in a packed bed. Resolved fluid flow e.g. composition and temperature in the void space of a packed bed. Coupling between particulate and gas phase for heat, mass and momentum transfer. Innovative numerical approach to investigate into packed bed processes Analysis of detailed results allows to uncover the underlying physics in packed bed processes.